Optical properties of novel photosensitizers for photodynamic therapy - Aslanoğlu, Busenur. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Computational chemistry plays an important role in interpreting various phenomena regarding properties of complex molecular and biological systems via several computational approaches. In this thesis, the full characterization of the photophysical properties of the temoporfin chromophore(mTHPC) and newly designed metal coordinated photosensitizer candidate (Zn-Ar) will be investigated in the light of molecular modeling and simulation techniques presently used in photodynamic therapy. Notably, the photosensitizers follows different photophysical pathways which lead to intersystemcrossing and thus, the triplet state population occurs. This is essential for producing the singlet oxygen, which leads to cell death. In this thesis, molecular dynamics (MD) and quantum mechanics simulations, we employed to shed light on the formation of stable interactions between the temoporfin and the membrane; particularly, the penetration of temoporfin into its hydrophobic center. These processes will allow us to determine the specific interactions between temoporfin and the lipid oxidizable double bond pointing towards the production of singlet oxygen. In addition to temoporfin, a novel photosensitizer candidate was investigated with the same protocol. This novel photosensitizer candidate will expose the effects of the metal coordinated chromophores and their photodynamic therapy abilities.
Keywords: Photochemotherapy.; Computational chemistry.